Berat Badan, Panjang Badan dan Faktor Genetik sebagai Prediktor Terjadinya Stunted pada Anak Sekolah - Hetriana Leksananingsih; Slamet Iskandar; Tri Siswati (Poltekkes Kemenkes Yogyakarta, 2017)
Background: Riskesdas in 2013 showed that Yogyakarta (DIY) had a prevalence of stunted new kid in school is less than the national average, which is 14.9% (MOH, 2013). Stunted or short, is a linear growth retardation has been widely used as an indicator to measure the nutritional status of individuals and community groups. Stunted can be influenced by several factors: birth weight, birth length match and genetic factors. Objective: To determine the weight, length of low birth weight and genetic factors as predictors of the occurrence of stunted on elementary school children. Methods: The study was a case control analytic. Research sites in SD Muhammadiyah Ngijon 1 Subdistrict Moyudan. The study was conducted in May and June 2015. The subjects were school children grade 1 to grade 5 the number of cases as many as 47 children and 94 control children. With the inclusion criteria of research subjects willing to become respondents, was present at the time of the study, they have a father and mother, and exclusion criteria have no data BB and PB birth, can not stand upright. The research variables are BBL, PBL, genetic factors and TB / U at this time. Data were analyzed by chi-square test and Odd Ratio (OR) calculation. Results: In case group as much as 91.5% of normal birth weight and length of 80.9% of normal birth weight, most of the height of a normal mother and father as many as 85.1%. In the control group as much as 78.7% of normal birth weight and 61.7% were born normal body length, height mostly normal mom and dad that 96.7% of women and 90.4% normal normal father. Statistical test result is no significant correlation between height mothers with stunted incidence in school children, and the results of chi-square test P = 0.026 with value Odd Ratio (OR) of 3.9 and a range of values from 1.091 to 14.214 Cl95%. Conclusion: High maternal body of mothers can be used as predictors of the occurrence of stunted school children and mothers with stunted nutritional status have 3.9 times the risk of having children with stunted nutritional status. Keywords: BBL, PBL, Stunted, Schoolchildren